1999
DOI: 10.2466/pms.1999.89.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the National Curriculum for Physical Education on Inner-City Teachers' Behaviours Associated with Pupils' Psychosocial Development

Abstract: This study examined the quality of instruction provided by a sample of teachers working in a depressed urban setting and within the confines of the National Curriculum for Physical Education in terms of use of behaviours related to pupils' psychosocial development. Subjects were 18 specialist physical education teachers working in seven mixed-sex secondary schools in one large city in southeastern England. Two lessons of each teacher's choice, in which they taught any activity to pupils in Years 7, 8, or 9, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…The work of Curtner- Smith and Hasty (1997) was extended by Curtner- Smith et al (2001). Results concluded that teachers were still working in a very similar way though one difference was that teachers in the second study used practice style significantly more than the first group and managed their classes significantly less.…”
Section: Literaturementioning
confidence: 98%
See 3 more Smart Citations
“…The work of Curtner- Smith and Hasty (1997) was extended by Curtner- Smith et al (2001). Results concluded that teachers were still working in a very similar way though one difference was that teachers in the second study used practice style significantly more than the first group and managed their classes significantly less.…”
Section: Literaturementioning
confidence: 98%
“…According to Goldberger and Howarth (1992) the Spectrum of Teaching Styles and the National Curriculum are key elements in the teaching and learning process. The only studies to date which looked specifically at the influence of the National Curriculum on teaching styles were the work of Curtner- Smith and Hasty (1997) and Curtner-Smith et al (2001). Curtner- Smith and Hasty's (1997) research investigated whether the initial introduction and implementation of the NCPE (1992) led to teachers expanding their range of teaching styles.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations